Ten on the sled - Norman, Kimberly; Woodruff, Liza (New York : Sterling, 2010)
Animals fall off a speeding sled one by one until only a lonely caribou is left, chasing a giant snowball that has engulfed the falling animals.
Keywords: Stories in rhyme; Sleds -- Juvenile fiction; Sledding -- Juvenile fiction; Animals -- Juvenile fiction; Counting -- Juvenile fiction